Coffee Shop Marketing Innovation through Differentiation Strategies during COVID-19 - Pristiyono Pristiyono; Husain Husain; Aziddin Harahap (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The aim of this research is to dig deeper into differentiation strategies through appropriate indicators and what differentiation is offered by coffee shop business actors. Based on data from the Labuhanbatu Regency Cooperatives and SMEs Service in 2021, currently, the number of MSMEs operating in coffee shops is still surviving and is recorded as being actively assisted by 156 MSMEs. So, the authors decided to use the entire population as a sample of 156 respondents. Determination of sampling applies purposive sampling, one of the non-random sampling techniques. Data analysis uses validity and reliability tests as well as problem-solving using the IBM SPSS AMOS 22 path analysis approach. Based on the results of the respondent profile description, it is known that the majority are male, aged 31-40 years. The majority of businesses last 7-10 years with owner status. All hypotheses in this research can be accepted so that the variables of product differentiation, price differentiation, and service differentiation have a significant effect on marketing innovation.